Pendekatan Efektif dalam Manajemen Konflik di Madrasah - Solechan Solechan; Mar'atul Azizah; Dewi Lestari (LP3M IAI Al Urwatul Wutsqo Jombang, 2024)
This research aims to examine the sources of conflict and strategies implemented by madrasa heads in managing conflict at MTs Al Washoya, Ngoro, Jombang. The research method used is a qualitative descriptive approach. Data was collected through observation techniques, in-depth interviews and document analysis, in order to obtain a comprehensive understanding of the source of the conflict and the madrasa head's strategy in resolving it. The results of the research show that the source of conflict arises from the first internal factor, the absence of teachers without notification and the lack of attendance of most teachers at meetings. Secondly, the unequal distribution of tasks has resulted in excessive workload for some teachers and staff. The third issue is interpersonal relations. Some teachers felt offended when they were reprimanded by picket teachers. The strategy used by madrasah heads in handling conflict is by carrying out several stages, namely analysis of the level of conflict that occurs, including identifying the characteristics of the conflict, the type of conflict, its causes and the actors involved. Next, identify the source of the problem, to understand the roots of the conflict that occurs. Then the conflict resolution process involves summoning the conflicting party for questioning and giving a personal warning. Lastly, carry out an evaluation by communicating with the parties in conflict to ensure that the solution provided resolves the conflict